2002
DOI: 10.1021/bi0121407
|View full text |Cite
|
Sign up to set email alerts
|

Rotational-Echo Double Resonance Characterization of Vancomycin Binding Sites in Staphylococcus aureus

Abstract: Solid-state NMR experiments with stable isotope-labeled Staphylococcus aureus have provided insight into the structure of the peptidoglycan binding site of a potent fluorobiphenyl derivative of chloroeremomycin (Eli Lilly LY329332). Rotational-echo double resonance (REDOR) NMR provided internuclear distances from the 19F of this glycopeptide antibiotic to natural-abundance 31P and to specific 13C and 15N labels biosynthetically incorporated into the bacteria from labeled alanine, glycine, or lysine in the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
193
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 83 publications
(208 citation statements)
references
References 60 publications
13
193
0
Order By: Relevance
“…In fact Kim et al [42] have recently demonstrated by rotational-echo double resonance of vancomycin binding sites in Staphylococcus aureus that glycopeptide antibiotics might not form dimers in-situ in mature peptidoglycan. Furthermore, they postulate that the sugar interactions with the glycans of the cell wall stabilize the monomeric complex.…”
Section: Discussionmentioning
confidence: 99%
“…In fact Kim et al [42] have recently demonstrated by rotational-echo double resonance of vancomycin binding sites in Staphylococcus aureus that glycopeptide antibiotics might not form dimers in-situ in mature peptidoglycan. Furthermore, they postulate that the sugar interactions with the glycans of the cell wall stabilize the monomeric complex.…”
Section: Discussionmentioning
confidence: 99%
“…aureus cells were grown in 300 ml of defined media (20) containing [1][2][3][4][5][6][7][8][9][10][11][12][13] C]glycine and L-[ε -15 N]lysine. The cells were harvested at OD 660 = 1.0 and were complexed with 6.7 mg (4.0 μmoles) of FPBV, resulting in 66% cell-wall binding-site occupancy (15). A second sample contained 6.7 mg LY309687 (3.7 μmol) complexed with whole cells for 60% binding-site occupancy.…”
Section: Growth Of Cells and Formation Of Complexesmentioning
confidence: 99%
“…The calculated dephasing is from five independent 13 C-19 F pairs (15). The weak 13 C- 13 C coupling between carbonyl carbons of the pentaglycyl bridging segment is totally suppressed by fast magic-angle spinning, and the 3-bond J coupling is less than 10 Hz.…”
Section: Fpbv Complex With [1-13 C]gly-labeled Whole Cellsmentioning
confidence: 99%
See 2 more Smart Citations